Development of a Mobile Learning E-book on Islamic Integrated Human Circulatory System for Class VIII SMP/MTs Students - Mochammad Ricky Rifa'i; Rafiatul Hasanah (Bioeducation Journal, 2022)
The purpose of this research and development is to describe the results of the validity and response of mobile learning e-books on the material of the Islamic integrated human circulatory system for class VIII SMP/MTs students. The method used is research and development with a 4-D model by Thiagarajan which includes four stages, namely define, design, development, and dissemination. However, in this research it is limited to the development stage. The subjects of this research include validators and students. The validators include material experts, media experts, Al-Qur'an and Tafsir experts, and practitioners. The object of this research is class VIII-C students of SMP Negeri 1 Tempeh, Lumajang Regency which is divided into two stages in the response test, namely a small scale of 10 students and a large scale of 30 students. The data analysis technique used is descriptive analysis in the form of expert validation instruments and student responses using a Likert scale. The results showed that the mobile learning e-book was feasible based on the percentage of material experts by 94%, media experts by 95%, experts in Al-Qur'an and Tafsir science by 95%, and teachers by 96%. Also obtained from the results of student responses on a small scale to get a percentage of 91% and a large scale of 94%. This means that in terms of readability and attractiveness, it is very interesting and feasible to be applied in learning. Overall, mobile learning e-books can be said to be very valid and interesting to apply in learning activities for the human circulatory system.